Formation of accounting and analytical support for managing financial and economic security of an agricultural enterprise - Vasilieva, Lesya; Васільєва, Леся Миколаївна (Дніпровський державний аграрно-економічний університет, 2025)
The stages of creation and implementation of the system of accounting and analytical support of financial and economic security of enterprise are defined. It forms methodical approaches to creation of an analytical basis for management of financial and economic security of agrarian enterprises. The stages of development and implementation of the strategy of financial and economic security of the agrarian enterprise are substantiated. Визначено етапи створення та впровадження системи обліково-аналітичного забезпечення фінансово-економічної безпеки підприємства. Сформовано методичні підходи до створення аналітичної основи управління фінансово-економічною безпекою аграрних підприємств. Обґрунтовано етапи розробки та реалізації стратегії фінансово-економічної безпеки аграрного підприємства.
Формування обліково-аналітичного забезпечення управління фінансово-економічною безпекою сільськогосподарського підприємства
Keywords: risks; ризики; management; управління; economic security; економічна безпека; analytical support; аналітичне забезпечення